2021
DOI: 10.7150/jca.58250
|View full text |Cite
|
Sign up to set email alerts
|

ALDH3A1 driving tumor metastasis is mediated by p53/BAG1 in lung adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD) is a lethal malignancy with metastasis, a major tumor feature that predominantly correlated with progression, but the molecules that mediated tumor metastasis remain elusive. To declare the critical regulatory genes, RNA sequencing data in LUAD patients was acquired from The Cancer Genome Atlas (TCGA) and found that ALDH3A1 was distinctly highly expressed in LUAD patients with metastasis (M1) compared with those without metastasis (M0), linked to the property of cancer stem cell and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Our data, demonstrating higher levels of total and phospho-p53 along with lower DNA damage and apoptosis levels in the ALDH3A1/HCE-2 cells, are in agreement with this hypothesis. In accordance with our findings, Fan et al (2021) reported that ALDH3A1 was positively associated with the total p53 in tissues of lung adenocarcinoma and that a knockdown of ALDH3A1 in the lung adenocarcinoma cell line A549 resulted in lower protein levels of total p53 [ 40 ]. Similarly, Koppaka et al (2016), demonstrated that expression of ALDH3A1 in the corneal epithelium hTCEpi cell line was associated with increased cytosolic and nuclear p53 levels.…”
Section: Discussionsupporting
confidence: 92%
“…Our data, demonstrating higher levels of total and phospho-p53 along with lower DNA damage and apoptosis levels in the ALDH3A1/HCE-2 cells, are in agreement with this hypothesis. In accordance with our findings, Fan et al (2021) reported that ALDH3A1 was positively associated with the total p53 in tissues of lung adenocarcinoma and that a knockdown of ALDH3A1 in the lung adenocarcinoma cell line A549 resulted in lower protein levels of total p53 [ 40 ]. Similarly, Koppaka et al (2016), demonstrated that expression of ALDH3A1 in the corneal epithelium hTCEpi cell line was associated with increased cytosolic and nuclear p53 levels.…”
Section: Discussionsupporting
confidence: 92%
“…Immune responses might target metabolic pathways in anticancer immunotherapy by metabolic reprogramming of immune or cancer cells [15]. ALDH3A1 had potential contribution to proliferation, cellular metabolism, and apoptosis suppression [16]. Clinical survival analysis also demonstrated that high ALDH3A1 expressions were associated with bad prognosis of lung cancer patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…ALDH3A1, a member of the superfamily of NAD(P)+-dependent enzymes, can oxidize diverse aldehydes into carboxylic acids ( 72 ). ALDH3A1 shows depletion in kidney fibroblasts after TGF-β treatment ( 73 ).…”
Section: Discussionmentioning
confidence: 99%